PENGARUH ATRIBUT PRODUK DAN REFERENSI KOMUNITAS TERHADAP MINAT BELI ULANG PADA KAFE KOPI MIRING DI SEMARANG - Agy Nilawati, Nandia; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2012)
The research was motivated by the growing business of serving food, especially in the form of cafes in the city of Semarang that influence the buying decisions of consumers buying interest again. Buying interest again indicate a high level of customer satisfaction in making a purchase and consumption. Based on sales data in 2011 and early 2012 show that sales have fluctuated Kopi Miring. Therefore, we find two variables that influence consumer buying interest over the attributes of the product and reference communities that are used in this study. The purpose of this study was to determine whether the attributes of the product and the reference community influence over consumer buying interest Kopi Miring. Population used in this study is the Kopi Miring consumers who make purchases of three or more times. Samples in this study as many as 96 respondents using simple random sampling method which happens to be in the Kopi Miring. Analysis of data obtained in the form of quantitative and qualitative analysis. These results indicate that all the independent variables together in a positive effect on re-buying interest and positive influence on an individual basis against buying interest again. Thus, product attributes and reference the community has a positive and significant impact on consumer buying interest again in Kopi Miring Semarang indicate variables which influence the value of 42.5%.